Influences of Various Factors on Inducing Adventitious Shoot Regeneration From Stem Explants of Cassia Mimosoides Linn. - Liu, Ying; Zhou, Yuan hang; Liao, Zi xin; Liu, Hong jie; Zhao, Min; Chen, Jian ping; Yang, Ya li; Xue, Ying bin (Bangladesh Journal of Botany, 2023)
In the present study, an efficient plant regeneration method was established in Cassia mimosoides by using stem explants. Low regeneration frequency with poor quality advantageous shoot buds were obtained when the explants were grown only Kinetin (KN) or thidiazeuron (TDZ) enriched media. For improving the regeneration efficiency and production of good quality adventitious buds, Cu2+, Mg2+, Fe2+ and Ag+ were supplemented in the regeneration medium at different concentrations. The highest (63.96%) adventitious bud regeneration rate, the maximum number of buds (5.39) per explant and the longest regenerated buds (3.49 cm) were obtained by adding 26 mg/l Ag+ in the regeneration medium. In order to improve the rooting in shoot buds, diethyl aminoethyl hexanoate (DA-6) at different concentrations was added into rooting medium. The optimal rooting was obtained by supplementing 0.6 mg/l DA-6. The highest rooting rate (90.23%), the highest number of roots per bud (6.08) and the longest roots (4.26 cm) were developed within 20 days of culture in this medium. By applying this method culture cycle for obtaining complete regenerated plantlets was significantly shortened (in 60 days), Additional culture for proliferation and elongation of regenerated adventitious buds was not needed. Therefore, the method established in the present study was helpful to improve the efficiency of plant regeneration from stem explants in C. mimosoides. Besides the establishment of this culture method could lay a foundation for the future large-scale cultivation and genetic transformation of C. mimosoides. Bangladesh J. Bot. 51(4): 873-882, 2022 (December) Special